Study of Solid Particles Properties In Influencing Erosion of Gas Turbine Using Computational Fluid Dynamics - Yap, Hong Yi (IRC, 2021)
Erosion is a process whereby an equipment, machine or any object experiences wear and tear due to repetitive impacts caused by particles (normally carried by a fluid) onto the surface of it, causing the material on the surface of the part to be removed from it.